Staying True to the Data - Ilse Doyer; Michael K. Ayomoh (Grounded Theory Review: An International Journal)
This paper describes a data-based and transparent approach that was followed during classic grounded theory data analysis to ensure rigor and theoretical saturation. Firstly, a visual approach was followed to ensure that the theory discovery stayed as close to the story told by the data set as possible, thus ensuring both rigor and accuracy. Secondly, process data in the form of a coding rate time study and theoretical contribution rate, were tracked to monitor theoretical saturation objectively. The presented approach offers a novel approach to showcasing classic grounded theory rigor during the data coding process, as well as a way to prove that theoretical saturation was reached. The approach presented in this paper thus provides grounded theory researchers with a way in which to both ensure and defend the rigor and accuracy of their research.